Investigation of antimony adsorption on a zirconium-porphyrin-based metal–organic framework. Issue 39 (16th September 2021) - Guo, Ying; Zhang, Xinyue; Xie, Nianyi; Guo, Rongxiu; Wang, Yao; Sun, Zejun; Li, Hong; Jia, Hongna; Niu, Dun; Sun, Hong-bin
Abstract : The porphyrin ring and the zirconium cluster contribute to the rapid, efficient and pH-dependent adsorption of antimony by PCN-222. Abstract : A zirconium-porphyrin based organic framework PCN-222 was employed for investigating the adsorption performance of Sb(iii ) in aqueous solution. It is proved that the adsorbent has the advantages of rapid adsorption and high capacity. Interestingly, we discover that PCN-222 shows pH-dependent adsorption performance, with higher capacity at pH = 2 and 8 than at pH = 5. According to XPS and FT-IR analyses, an adsorption model of PCN-222 with pH = 2, 5, and 8 is proposed, that is, zirconium clusters combine with antimony at different pH values with bidentate complexes, monodentate complexes, and alkaline monodentate complexes, thus producing an excellent adsorption effect. Moreover, the porphyrin ring is also beneficial for the adsorption of antimony. In addition, PCN-222 shows good regeneration and recycling performance, and it is a promising adsorbent as well as a platform for investigating the removal of Sb(iii ) in water treatment.